Costs of denied health care services and of the lawsuits filed to obtain them in Medellín, 2009 - Emmanuel Nieto L; Alejandro Arango C (Universidad de Antioquia, 2011)
Objective: to retrace the legal route of writs for the protection of constitutional rights involving health care services and to determine the cost of such processes and those of the health care services invoked in a sample of such writs taken in Medellín city. Methods: a descriptive study with a qualitative focus for retracing the legal route of the writs, and a quantitative approach for the purpose of cost estimation. The 2009 SOAT (Mandatory Car Insurance) fees were used for assessing the cost of the health care services. As for the assessment of the legal costs, we used the micro-costing approach together with the activity-based costing methodology. Results: for each $100 corresponding to the cost of the services denied by the health care services provider, the Medellín judicial system spent around $48 on each legal process. In more than half of the cases, the cost of the legal action was higher than the services' cost. Discussion: the cost of the legal process involving the writs for the protection of constitutional rights regarding health care services that were filed in the country between 1999 and 2009 could represent 2% of the budget circulating throughout the entire health system. This cost is just a part of the transaction costs generated by the health care services providers' breach of the social contract established by the Colombian Constitution. Furthermore, in most cases there is also a breach of the private contract between these service providers and the health system users.